Electrostatically Interactive Injectable Hydrogels for Drug Delivery - Seo, Ji Young; Lee, Bong; Kang, Tae Woong; Noh, Jung Hyun; Kim, Min Ju; Ji, Yun Bae; Ju, Hyeon Jin; Min, Byoung Hyun; Kim, Moon Suk (Tissue Engineering and Regenerative Medicine, 2018)
Background:: Several injectable hydrogels have been developed extensively for a broad range of biomedical applications. Injectable hydrogels forming in situ through the change in external stimuli have the distinct properties of easy management and minimal invasiveness, and thus provide the advantage of bypassing surgical procedures for administration resulting in better patient compliance. Methods:: The injectable in situ-forming hydrogels can be formed irreversibly or reversibly under physiological stimuli. Among several external stimuli that induce formation of hydrogels in situ, in this review, we focused on the electrostatic interactions as the most simple and interesting stimulus. Results:: Currently, numerous polyelectrolytes have been reported as potential electrostatically interactive in situ-forming hydrogels. In this review, a comprehensive overview of the rapidly developing electrostatically interactive in situ-forming hydrogels, which are produced by various anionic and cationic polyelectrolytes such as chitosan, celluloses, and alginates, has been outlined and summarized. Further, their biomedical applications have also been discussed. Conclusion:: The review concludes with perspectives on the future of electrostatically interactive in situ-forming hydrogels.
Keywords: Biomedical applications; Cationic polyelectrolyte; External stimulus; In-situ forming; Injectable; Injectable hydrogels; Patient compliance; Surgical procedures; Drug delivery; Electrostatic interactions; In situ-forming hydrogels; Injectable; Regenerative medicine